1998
DOI: 10.1128/aem.64.3.960-969.1998
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Structure of the Methanogenic Community in Anoxic Rice Paddy Soil Microcosms as Examined by Cultivation and Direct 16S rRNA Gene Sequence Retrieval

Abstract: A dual approach consisting of cultivation and molecular retrieval of partial archaeal 16S rRNA genes was carried out to characterize the diversity and structure of the methanogenic community inhabiting the anoxic bulk soil of flooded rice microcosms. The molecular approach identified four groups of known methanogens. Three environmental sequences clustered with Methanobacterium bryantii andMethanobacterium formicicum, six were closely related but not identical to those of strains of Methanosaeta concilii, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
310
2
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 630 publications
(324 citation statements)
references
References 73 publications
10
310
2
2
Order By: Relevance
“…Triplicate samples were used to extract DNA and analyse the terminal restriction length polymorphism (T-RFLP) of archaeal 16S rRNA genes (see Chin et al, 1999) using 109f/ 915r as the primer pair (Grosskopf et al, 1998). T-RFLP of archaeal 16S rRNA genes is a fingerprinting technique, which determines the lengths (base pairs: bp) and relative abundance of particular terminal restriction fragments (T-RF).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triplicate samples were used to extract DNA and analyse the terminal restriction length polymorphism (T-RFLP) of archaeal 16S rRNA genes (see Chin et al, 1999) using 109f/ 915r as the primer pair (Grosskopf et al, 1998). T-RFLP of archaeal 16S rRNA genes is a fingerprinting technique, which determines the lengths (base pairs: bp) and relative abundance of particular terminal restriction fragments (T-RF).…”
Section: Methodsmentioning
confidence: 99%
“…In rice-field soil, H 2 plus CO 2 can be utilized by several groups of methanogens, i.e. Methanobacteriales, Methanomicrobiales, Methanosarcinaceae and Rice Cluster I (RC-I) (Grosskopf et al, 1998), that were found to occur in such soils from various geographic locations (Ramakrishnan et al, 2001). RC-I methanogens are a deeply branching group of methanogens, which have so far not been isolated into pure culture but have recently been characterized genomically (Erkel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…DNA extraction from Methanobacterium sp. Bab-1 and the methanogenic consortia enriched on H 2 and ethanol, respectively, was performed as described by Großkopf et al (1998b). Partial SSU rDNA from strain Bab-1 was amplified via PCR using the forward primer 109F (5Ј-GCTCAGTAA-CACGTGG-3Ј; Großkopf et al, 1998b) and the reverse primer 1391R (5Ј-GACGGGCGGTGTGTRCA-3Ј; Lane, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the methanogenic community in the bulk soil is dominated by Methanosaeta spp. (Großkopf et al, 1998b), that on the roots of the rice plants is dominated by other methanogenic taxa (Großkopf et al, 1998a).…”
Section: Fig 5 Evolutionary Distance Dendrogrammentioning
confidence: 99%
“…The SSU rDNA fraction of the DNA samples was amplified by PCR with the archaeal-specific primers described by Groûkopf et al (1998a), which amplifies from position 109± 934 (Escherichia coli 16S rRNA numbering; Brosius et al, 1978) as described previously (Chin et al, 1999). The thermal profile used for amplification of slurry±DNA included 20 (for cloning, see below) and 28 (for T-RFLP) cycles of denaturation (30 s), primer annealing at 528C (1 min) and elongation at 728C (2 min).…”
Section: Amplification Of Archaeal Ssu Rrna Gene Fragments and T-rflpmentioning
confidence: 99%